2017
DOI: 10.1021/acschembio.6b01135
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite Binds to the RING Finger Domain of FANCL E3 Ubiquitin Ligase and Inhibits DNA Interstrand Crosslink Repair

Abstract: Human exposure to arsenic in drinking water is known to be associated with the development of bladder, lung, kidney, and skin cancers. The molecular mechanisms underlying the carcinogenic effects of arsenic species remain incompletely understood. DNA interstrand cross-links (ICLs) are among the most cytotoxic type of DNA lesions that block DNA replication and transcription, and these lesions can be induced by endogenous metabolism and by exposure to exogenous agents. Fanconi anemia (FA) is a congenital disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
(98 reference statements)
2
26
0
Order By: Relevance
“…In light of the previous observations about the effects of As(III) binding on modulating the E3 ubiquitin ligase activities of other RING finger proteins, [20][21][22]25 we reasoned that the decreases in ubiquitination of RPS10 and RPS20 may be attributed to the interaction between As(III) and ZNF598 and the ensuing loss of its E3 ubiquitin ligase activity. To test this, we first examined the interaction between As(III) and ZNF598.…”
Section: ■ Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…In light of the previous observations about the effects of As(III) binding on modulating the E3 ubiquitin ligase activities of other RING finger proteins, [20][21][22]25 we reasoned that the decreases in ubiquitination of RPS10 and RPS20 may be attributed to the interaction between As(III) and ZNF598 and the ensuing loss of its E3 ubiquitin ligase activity. To test this, we first examined the interaction between As(III) and ZNF598.…”
Section: ■ Resultsmentioning
confidence: 85%
“…16 To this end, we performed a quantitative proteomic experiment, which relies on metabolic labeling using SILAC and immunoprecipitation of tryptic peptides containing diglycine remnant-modified lysine(s), and LC-MS/MS analysis, to identify proteins in GM00637 human skin fibroblasts exhibiting substantial alterations in their ubiquitination levels after a 24 h exposure to 5.0 μM NaAsO 2 (Figure 1A). 25 We found that the ubiquitination levels of lysine 138 and 139 (K138 and K139) in RPS10 and K8 in RPS20 were decreased to 60% and 52% of the levels observed in control untreated cells, respectively (Figure 1B). Representative MS and MS/MS results for monitoring the ubiquitination of K8 in RPS20 are shown in Figure 2, and the MS/MS for monitoring the ubiquitinations of K138 and K139 in RPS10 are shown in Figure S1.…”
Section: ■ Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…6 Since most RING finger domains harbor a C3H- and a C4-type zinc finger, 79 our recently published work demonstrated the interactions between arsenite and the RING finger domains of proteins, including several E3 ligases, such as FANCL and RNF20-RNF40, which ultimately led to the inhibition of the repair of DNA interstrand cross-link lesions and double strand breaks, respectively. 10,11 Our previous work also elucidated the interaction between arsenite and the zinc finger motifs of Tip60 histone acetyltransferase and ten-eleven translocation (Tet) family proteins, which perturbs histone and DNA epigenetic marks. 12,13…”
Section: Introductionmentioning
confidence: 99%